CHARACTER EVOLUTION OF THE BENTHIC THECATE DINOFLAGELLATE, GAMBIERDISCUS (DINOPHYCEAE), WITH AN INTRODUCTION OF THE INTERACTIVE KEY TO SPECIES - Mustapa, Nurin Izzati; Sing, Tung Teng; Toh, Hii Tan; Hong, Chang Lim; Po, Teen Lim; Chui, Pin Leaw (Malaysian Journal of Science, 2015)
The genus Gambierdiscus is one of the benthic marine dinoflagellates that are known to produce biotoxins, causing ciguatera food poisoning (CFP) in humans after consuming the contaminated marine fishes. These benthic marine dinoflagellates are commonly found in the warm tropical and subtropical waters. The phenomena associated with high cell abundance or â€œbloomsâ€ is referred to Benthic Harmful Algal Blooms (BHABs). Precise species identification is crucial as not all of the species in the genus are toxic. In this study, morphological characteristics of Gambierdiscus species widely used in species identification were analyzed, and the character states coded. Taxon sampling on the large subunit (LSU) rDNA of all Gambierdiscus species were carried out, and used for the phylogenetic reconstruction. The character states were mapped onto the Maximum Parsimony (MP) tree to investigate the character state evolution of Gambierdiscus species. Morphological information and the distribution of the 13 species were used to develop a comprehensive taxonomic database of Gambierdiscus, a web-based interactive identification key for species identification is presented. ABSTRACT Genus Gambierdiscus adalah salah satu dinoflagelat bentik marin yang menghasilkan biotoksin penyebab keracunan ikan ciguatera (CFP) pada manusia akibat termakan ikan marin yang tercemar. Dinoflagelat ini biasanya ditemui di perairan tropika dan subtropika yang panas. Fenomena ini yang berkaitan dengan kepadatan sel yang tinggi atau ledakan adalah dirujuk sebagai â€œBenthic Harmful Algal Bloom (BHAB)â€. Pengecaman spesis yang tepat adalah penting kerana tidak semua spesies dalam genus ini adalah beracun. Dalam kajian ini, ciri-ciri morfologi digunakan secara meluas dalam pengecaman spesies Gambierdiscus telah dianalisa, dan pengkodan keadaan ciri-ciri ditentukan. Persampelan takson jujukan ribosamal subunit besar (LSU) rDNA semua spesies Gambierdiscus telah dijalankan, dan digunakan untuk pembinaan semula filogenetik. Keadaan ciri-ciri telah dipetakan ke atas pokok kekikiran maksimum (MP) untuk mengkaji evolusi keadaan ciri morfologi spesies Gambierdiscus. Maklumat morfologi 13 spesies dan taburan mereka telah digunakan untuk menghasilkan pangkalan data taksonomi Gambierdiscus yang komprehensif. Kekunci pengecaman spesies interaktif sesawang untuk tujuan pengecaman dibentangkan. Keywords: Benthic dinoflagellates; ciguatera; harmful; interactive key; morphological characters